Penerapan Metode Qawaid Wa Tarjamah Untuk Meningkatkan Pemahaman Struktur Bahasa Arab Dasar Mabni Dan Mu’rab - Surya Hidayat; Doni Sastrawan; Khairil Anwar (Program Studi Pendidikan Bahasa Arab, 2022)
This research is based on the low understanding of students in Arabic material, especially in mabni and mu'rab in the structure of Arabic. The method that the researchers used was